2020
DOI: 10.3389/fnmol.2020.586169
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Tau Protein: New Insights and Future Directions

Abstract: Tau is a microtubule-associated protein (MAPT) that is highly expressed in neurons and implicated in several cellular processes. Tau misfolding and self-aggregation give rise to proteinaceous deposits known as neuro-fibrillary tangles. Tau tangles play a key role in the genesis of a group of diseases commonly referred to as tauopathies; notably, these aggregates start to form decades before any clinical symptoms manifest. Advanced imaging methodologies have clarified important structural and functional aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Thus, the need for non-toxic uorescence dyes bearing better selectivity, a nity, and speci city for tau proteins is fostering the development of a novel generation of tracers 25,26 . In this regard, the recent characterization of tau protein structure at the atomic 27,28 might represent an outstanding milestone for better tackling such needs 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the need for non-toxic uorescence dyes bearing better selectivity, a nity, and speci city for tau proteins is fostering the development of a novel generation of tracers 25,26 . In this regard, the recent characterization of tau protein structure at the atomic 27,28 might represent an outstanding milestone for better tackling such needs 29 .…”
Section: Introductionmentioning
confidence: 99%
“…19,21 These studies have enabled structure based classification of Tauopathies, thus paving the way for a rational design of disease-specific therapeutics and and diagnostics. 575 Recently, Cryo-EM was used to directly map the ligand-binding sites within the AD Tau fold. 576 It showed that fibril core residues in multiple diseases primarily comprise the MTBR repeats R3 and R4, which is important in designing the antibodies with epitopes directed outside of these regions.…”
Section: How Can the New Biochemical And Structural Insights Into Physiological And Pathogenic Tau Inform Drug Discovery?mentioning
confidence: 99%
“…In all clinical trials on AD, inclusion criteria from patient enrollment to concluding evaluation at the end of the study, require careful evaluation of suitable biomarkers 4 . MRI is the most common entry-level analysis collected as an outcome measure, followed by amyloid PET and tau PET 4 6 . The current trend for novel clinical trials, however, increasingly requires advances in ultra-sensitive methods to detect proteins in cerebrospinal fluid (CSF) and plasma that enable the identification of pathological changes along the AD continuum.…”
Section: Introductionmentioning
confidence: 99%